Germany’s Polycentric Metropolitan Regions in the World City Network - Münter, Angelika (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
On a regional scale, two types of polycentricity can be observed. The first involves polycentric metropolitan regions that have evolved in the course of post-suburban development around a previously monocentric city, whereas the second type involves neighbouring metropolises evolving into a multi-core polycentric metropolitan region due to an increase in the functional interaction between each other. The German urban system is characterised by both types of polycentricity. In this paper I examine the role of these two types of polycentricity within the context of globalisation. I address the question of whether individual metropolitan cores and metropolitan cores and their associated post-suburban areas share the global functions of a metropolitan region or whether such functions are concentrated in a single city within the metropolitan region. To this end, I analyse the locations of leading global advanced producer service firms in Germany in their role as sub-nodes of the world city network. Finally, I discuss the empirical findings in the context of modelling the world city network.
Keywords: Polycentricity; Metropolitan regions; World city network; Germany